Meaningful ciphertext encryption algorithm based on bit scrambling, discrete wavelet transform, and improved chaos. Issue 5 (30th December 2020) - Jing, Shiwei; Guo, Yuan; Chen, Wei
Abstract: This paper proposes a meaningful ciphertext encryption algorithm of good practicability and strong robustness. The plaintext undergoes pre‐encryption of bit scrambling and secondary encryption of discrete wavelet transform (DWT) to obtain meaningful ciphertext. In the pre‐encryption stage, only the higher three bit pages that are not all 0 or 1 are scrambled. The embedding method in the secondary encryption process is to add the hundreds and tens' digit and ones' digit of the middle ciphertext to the scrambled detail information obtained by DWT of the cover image. The information entropy of the intermediate ciphertext obtained by this method can reach 7.997, the correlation coefficient between the ciphertext and the cover image can reach 0.99, and the decrypted image of the ciphertext under high‐intensity pollution can still be identified. It shows that the pre‐encryption can conceal the plaintext information well, and the secondary encryption can eliminate the ciphertext texture characteristics while retaining the good robustness. Finally, the improved three one‐dimensional chaos are used to generate random sequences, and the plaintext hash value is associated with the chaotic key. The improved chaos greatly improves the randomness of the sequence and broadens the range of parameters. The hash value SHA‐256 of the plaintext is added to make the key stream adaptively change with the plaintext, which greatly improves the sensitivity of the plaintext and the ability to resist selected plaintext and ciphertext attacks. Experiments have also verified that the encryption algorithm can encrypt images of different types and shapes and has strong practicability, good bit scrambling effect, and high sensitivity to scrambling.